2022
DOI: 10.3390/su142013223
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation of Heavy Metals in a Soil–Plant System from an Open Dumpsite and the Associated Health Risks through Multiple Routes

Abstract: Screening various plant species to act as hyperaccumulators and associated health risks could serve as a sustainable solution for the bioremediation heavy metals (HMs). For the first time, the present study explored the phytoremediation potential of native plants, soil enrichment, and human health risks associated with the contamination of HMs in soil and plant samples collected from a municipal solid-waste open dump site. Soil and plant samples (n = 18 + 18) from the dumpsite and (n = 18) from the control sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 64 publications
3
19
0
Order By: Relevance
“…Based on the results of this diagram between the aerial parts of the plant species Atriplex Verrucifera, Halocenemum Strobilaceum, Phragmites australis, Puccinella distans, and soil has a signi cant difference in Pb contaminants, and the amount of Pb in the aerial parts of these species is higher than the average of this element in the soil. Sabir et al (2022) reported the concentrations of Pb in plant roots and shoots ranged from 123 to 678 and 29 to 287 mg kg − 1, respectively. However, no signi cant differences were observed in the aerial parts of the species Achillea millefoliom, Cyperus longus, Scirpus lacustris, Typha latifolia and soil.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results of this diagram between the aerial parts of the plant species Atriplex Verrucifera, Halocenemum Strobilaceum, Phragmites australis, Puccinella distans, and soil has a signi cant difference in Pb contaminants, and the amount of Pb in the aerial parts of these species is higher than the average of this element in the soil. Sabir et al (2022) reported the concentrations of Pb in plant roots and shoots ranged from 123 to 678 and 29 to 287 mg kg − 1, respectively. However, no signi cant differences were observed in the aerial parts of the species Achillea millefoliom, Cyperus longus, Scirpus lacustris, Typha latifolia and soil.…”
Section: Discussionmentioning
confidence: 99%
“…A similar BAI value was found by Naz et al [ 38 ] who reported Pb in purslane up to 45 mg kg −1 in soil spiked with up to 500 mg Pb kg −1 . As for the TF, although values were much lower than 1.0, it must be stated that the TF > 1.0 requirement is seldom achieved by plants grown in soil [ 39 , 40 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…where E f is exposure frequency (365 days/year), E D is the exposure duration (65 years), equivalent to an average lifetime [47], and F IR is the average food (vegetable) consumption (240 g/person/day) which were obtained from the World Health Report (WHO, 2002) for low vegetable intake; C M is the metal concentration (mg/kg dry weight), C f is the concentration conversion factor for fresh vegetable weight to dry weight, i.e., 0.085 [48], B W is reference body weight for an adult, which is 70 kg [47], T A is the average exposure time (65 years × 365 days) and 0.001 is the unit conversion factor.…”
Section: Estimated Daily Intake (Edi)mentioning
confidence: 99%